Subjective meanings of the loneliness of people living with HIV - Dmitruk, I. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
The paper analyzes the experience of people’s, infected by HIV, loneliness as an existential category and as a part of all their spectrum of feelings and experiences. The central existential problem for people with HIV-positive status is social and interpersonal isolation, which brings to loneliness. There are no publications that highlight the loneliness of people, who lives with HIV, through the prism of an existential approach. The article also considers the problem of stigmatization, self-stigmatization and isolation of HIV-infected individuals. The situation is aggravated by the fact that terminally ill people not only experience negative emotions, but also realize their own guilt for infecting their illness, feel shame because of the negative social status of the "sinful" disease. People with HIV are a special subculture in our society; they often consider themselves as outcasts. Thanks to this research, the subjective meanings that have people with HIV put into the concept of loneliness are revealed. The author did her own semantic differential, which was helped in finding differences in the experience and understanding of loneliness by hypochondriacal people who are afraid of infecting HIV, as well as persons with a positive HIV status. The results of two groups were statistically handled by using factor analysis. As a result the components of the loneliness category for the control (hypochondriac) and experimental (people infected by HIV) groups were picked out. Eventually, hypochondriacal people actualize loneliness through the following factors: "anxiety-depression", "hopelessness" and "vulnerability". In turn, people with HIV-positive status, see loneliness through: "despair", "disgust" (directed both at oneself and at the outside world), and "rejection". The results can be explained by the fact that persons with HIV infection have already felt the consequences of social isolation and loneliness, therefore they describe themselves as outcasts, despair and disgust both to themselves and to others. While people who only afraid of contracting HIV predict this can lead to anxiety, hopelessness and vulnerability. However, the selected components are rather situational than a priori, so the picture may change somewhat upon repeated investigation.